1614 Iñupiaq Knowledge of Nanuq in the Southern Beaufort Sea - Hannah Voorhees (Research Workspace, 2019)
This data represents the words of local experts from Wainwright, Utqiaġvik, Nuiqsut, and Kaktovik. Indigenous knowledge provides insights on the responses of polar bears to sea ice loss. However, Traditional Ecological Knowledge (TEK) for the southern Beaufort Sea subpopulation has not been documented systematically since the 1990s. TEK is a dynamic body of knowledge that quickly responds to new conditions presented by climate change. Gaps in documentation have prevented TEK from entering fully into scientific research shaping management policies. This data closes this gap, providing an updated account of Iñupiaq knowledge about polar bears on the North Slope of Alaska. Local and traditional knowledge of polar bears was documented through semi-structured interviews in the communities of Wainwright (n =10), Utqiaġvik (n =13), Nuiqsut (n =12), and Kaktovik (n = 12) in 2017 and 2018. Interviews centered on maps of each community’s region and on individual life histories of observing bears while hunting on the land and ice. Participants included both experienced Elders and active subsistence hunters. Follow-up visits were conducted with participants in 2019 to verify initial findings. Themes covered in data include: changes in sea ice, wind, and weather; the impact of these changes on polar bears; polar bear body condition; local abundance; behavior; feeding; seasonal movement; habitat use; dens; cubs; and ice seals. Additional themes included aspects of human-polar bear relationships such as subsistence traditions and interactions between people and bears during whaling. Data focuses on knowledge of polar bears within the last fifteen years, seeking current observations as well as comparative assessments of change over time. Manifest of Media Products: Kaktovik_Fall_Winter.pdf Kaktovik_Fall_Winter.png Kaktovik_Spring_Summer.png Nuiqsut_Fall_Winter.pdf Nuiqsut_Fall_Winter.png Nuiqsuit_Spring_Summer.pdf Nuiqsut_Spring_Summer.png Overview_BeaufortSubPops_c.pdf Overview_BeaufortSubPops_c.png Utqiagvik_Fall_Winter.pdf Utqiagvik_Fall_Winter.png Utqiagvik_Spring_Summer.pdf Utqiagvik_Spring_Summer.png Voorhees 2019 TEK Report PRINT Wainwright_Fall_Winter.pdf Wainwright_Fall_Winter.png Wainwright_Spring_Summer.pdf Wainwright_Spring_Summer.png For each community, there are four maps of polar bear habitat use and denning areas. This includes one set of maps (in .pdf and .png) for Fall-Winter, and one set of maps (in .pdf and .png) for Spring-Summer. Fall- Winter is defined as September-February, Spring-Summer is defined as March-August. The Overview_BeaufortSubPops_c map depicts the range of the Southern Beaufort Sea polar bear subpopulation and the communities of the study.